2016
DOI: 10.1016/j.stemcr.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Down Syndrome Embryonic Stem Cells Reveals a Role for RUNX1 in Neural Differentiation

Abstract: SummaryDown syndrome (DS) is the leading genetic cause of mental retardation and is caused by a third copy of human chromosome 21. The different pathologies of DS involve many tissues with a distinct array of neural phenotypes. Here we characterize embryonic stem cell lines with DS (DS-ESCs), and focus on the neural aspects of the disease. Our results show that neural progenitor cells (NPCs) differentiated from five independent DS-ESC lines display increased apoptosis and downregulation of forehead development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…Furthermore, we observed that our DEGs are enriched for targets of RUNX1 (Enrichr: ENCODE and ChEA Consensus TFs from ChIP-X; adjusted p value 0.042) such as TGFB2 and EMP1 at both differentiation stages in line with previous reports (Supplementary Fig. 2) [38, 48].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we observed that our DEGs are enriched for targets of RUNX1 (Enrichr: ENCODE and ChEA Consensus TFs from ChIP-X; adjusted p value 0.042) such as TGFB2 and EMP1 at both differentiation stages in line with previous reports (Supplementary Fig. 2) [38, 48].…”
Section: Resultssupporting
confidence: 91%
“…3d). The strongest and most consistent upregulation at both differentiation stages was identified for RUNX1 encoding the transcription factor AML1 (average log2 fold change = 4.4), supporting its recently reported role in DS neurogenesis [38]. Together, these observations indicate that several DEGs on HSA21 implicated in neuronal functions strongly deviate from the predicted 3:2 levels in our trisomic model.
Fig.
…”
Section: Resultssupporting
confidence: 86%
“…RSUME down-regulation in spinal tissues of SOD1 G86R mice could negative impact motor units through these biological processes. Runx1 is a transcription factor stimulating neuronal differentiation and axonal plasticity and reduces BMP signaling and expression of Calca (Yoshikawa et al, 2015 , 2016 ; Halevy et al, 2016 ). Runx1 is a positive regulator of the expression of genes related to sphingolipid metabolism (Kilbey et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular and molecular mechanisms driving these different phenotypes are incompletely understood, altered stem cell function is a potential common link. For example, expansion and differentiation defects in neuronal stem cells impair neurogenesis in the developing brain and adult brain of individuals with Down syndrome 6 8 . Hematopoietic stem cells accumulate DNA damage, prematurely senesce and fail to expand in mouse models of Down syndrome 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%